Method for rapidly calibrating strength of geopolymer concrete through pH detection
The rapid calibration of the strength of geological polymer concrete through pH detection solves the problem of long detection time in the existing technology, realizes rapid strength evaluation and screening of geological polymer concrete, and promotes product marketing promotion.
Patent Information
- Application Number
- CN202411803679.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the strength detection of geological polymer concrete needs to be carried out after the curing is maintained until the corresponding age period, which takes a long time period and cannot be pre-calibrated, which affects the marketing and application of the product.
Quickly calibrate the strength of geological polymer concrete by pH detection, including mixing concrete raw materials, mixing samples with water, stirring and sieving, and detecting the pH value of the supernatant to determine the strength of the concrete.
The strength detection time of geological polymer concrete can be significantly shortened, and can be completed within 20 minutes, achieving prediction of strengths of different age periods, saving labor costs, and quickly screening out products that meet different application scenarios, promoting product promotion.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete detection, and in particular relates to a method for quickly calibrating the strength of geopolymer concrete through pH detection. Background Art
[0002] Geopolymer cementitious materials are inorganic cementitious materials formed by chemically stimulating potentially active aluminum silicate minerals, especially industrial solid waste metallurgical slag, through a series of physical and chemical reactions. The basic composition is CaO-M2O-Al2O3-SiO2-H2O, where M is an alkali metal. Compared with the production of ordinary Portland cement, the production of geopolymers avoids high-temperature (~1450 ℃) calcination, and some powder materials even avoid grinding power consumption, reducing comprehensive energy consumption and CO2 emissions by 40% to 90%.
[0003] Alkali-induced reaction is the main hydration reaction process of geopolymers. The alkalinity of its raw materials, such as alkali slag, can provide the required strong alkaline environment for the initial hydration in the reaction process, so it plays an important role in determining the formation of geopolymers. However, too low alkalinity in the system will cause insufficient strength development, and too high alkalinity will cause the compressive strength of the material to shrink, which will have an adverse effect on the development of later mechanical properties. In addition, since alkali slag is a small amount of raw materials (less than 3%) in the preparation of geopolymers, in the process of geopolymers being applied to concrete, the alkalinity in the system is easily affected by different raw material factors (for example, the manufacturer and batch of raw materials, etc.). In addition, external factors such as the storage environment or time will also affect the quality level of certain raw materials, resulting in certain fluctuations in the strength performance of different batches of geopolymer products, which will lead to the failure of the strength of geopolymer concrete to meet the requirements of higher concrete application scenarios, affecting the results of geopolymer products entering the client verification, and hindering the application and promotion of concrete products containing geopolymers in the market.
[0004] In the prior art, the strength level of concrete is mainly verified by testing the strength at a specific age after the concrete is cured. The disadvantages of this traditional method are that it takes a long time to adjust, is difficult, and consumes manpower and material resources. In addition, it is impossible to pre-calibrate the strength of concrete before the start of curing. The results can only be obtained after the concrete test block is cured to the corresponding age, which takes too long.
[0005] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0006] The purpose of the present invention is to provide a method for quickly calibrating the strength of geopolymer concrete by pH detection, so as to solve or improve the problem that when the source or quality of each raw material in the geopolymer concrete changes in the prior art, it is necessary to wait until the geopolymer concrete is cured to a corresponding age before the strength can be tested, which takes a long time. In addition, the method for quickly calibrating the strength of geopolymer concrete by pH detection of the present invention can also be used to quickly screen geopolymer products with different strength levels due to fluctuations in external factors, and provide them to concrete application scenarios with different strength requirements to achieve effective utilization and promotion of the products.
[0007] In order to achieve the above-mentioned object, the present invention provides the following technical solution: a method for quickly calibrating the strength of geopolymer concrete by pH detection, comprising the following steps: (1) after the raw materials of the geopolymer concrete are mixed uniformly to obtain a concrete mixture, a first sample is taken from different positions of the concrete mixture; (2) the first sample is mixed with water, stirred uniformly, and at least part of the aggregate in the first sample is removed by sieving to obtain a second sample; (3) the second sample is stirred, allowed to stand for stratification, and a supernatant is obtained; (4) the pH value of the supernatant is detected; and (5) the strength of the geopolymer concrete is judged according to the pH value detected in step (4).
[0008] Preferably, in step (2), the mass ratio of the first sample to water is 1:1-1:5; in step (3), the stirring speed is 1000-1500 r / min, the stirring time is 5-8 min, and the standing time is 5-10 min.
[0009] Preferably, in step (1), the number of portions of the first sample is 3-4, and the mass of each portion of the first sample is 50-60 g.
[0010] Preferably, in step (2), the sieve used for sieving is a standard square hole sieve of 0.15 mm.
[0011] Preferably, the raw materials of the geopolymer concrete include: geopolymer, mineral powder, fly ash, aggregate and water.
[0012] Preferably, the aggregate includes machine-made sand, fine sand, pebbles and large stones; the machine-made sand is coarse sand in zone I, the fine sand is extra-fine sand in zone III, the particle size of the pebbles is ≤5mm, and the particle size of the large stones is 10-20mm.
[0013] Preferably, the raw materials of the geopolymer concrete also include a water reducing agent.
[0014] Preferably, the concrete mixture is prepared by a method comprising the following steps: A. adding the geopolymer, mineral powder, fly ash and aggregate into a concrete mixer for dry mixing, stirring for 1-2 minutes to obtain a dry mixture; B. adding water to the dry mixture, stirring for 2-3 minutes to obtain the concrete mixture.
[0015] Preferably, in step B, a step of adding a water reducing agent is also included before stirring.
[0016] Beneficial effects: The method of the present invention for rapid calibration of the strength of geopolymer concrete by pH detection can generally be completed within 20 minutes. According to the result of the rapid calibration, the strength of concrete at different curing ages (for example, 1d, 3d, 7d or 28d) can be predicted, so as to solve or improve the problem in the prior art that when the source or quality of each raw material in the geopolymer concrete changes, it is necessary to wait until the geopolymer concrete is cured to the corresponding age before the strength can be detected, which takes a long time (when the method of the present invention is used for rapid calibration of the strength of geopolymer concrete 1d, the detection time of the strength of geopolymer concrete can be at least shortened to 1 / 72 of the original; correspondingly, when the method of the present invention is used for rapid calibration of the strength of geopolymer concrete 28d, the detection time of the strength of geopolymer concrete can be at least shortened to 1 / 2016 of the original).
[0017] The method for quickly calibrating the strength of geopolymer concrete by pH detection of the present invention can not only greatly save the manpower and maintenance time cost consumed in quality detection and raw material source screening of geopolymer concrete, but also realize the rapid screening of geopolymer products with different strength levels due to fluctuations of external factors, so that they can enter concrete application scenarios with different grade requirements respectively, which is helpful to solve the problem of popularization and application of geopolymers in concrete; the method for quickly calibrating the strength of geopolymer concrete by pH detection of the present invention not only helps to ensure the quality stability of geopolymer concrete, but also helps to conveniently realize the monitoring of the quality of each purchased raw material.
[0018] In addition, the method of the present invention for quickly calibrating the strength of geopolymer concrete by pH detection makes it possible to accurately judge whether the geopolymer concrete is within the optimal alkalinity range only based on the pH value test result of the concrete slurry after the concrete is evenly mixed, and to pre-calibrate the strength of the geopolymer concrete through different pH gradient ranges, thereby enabling the promotion and verification of the product to be accurately carried out according to the strength requirements of the concrete in actual applications. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0020] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0021] The present invention aims to solve the problem that when the sources or quality of raw materials in geopolymer concrete change in the prior art, the strength of the geopolymer concrete needs to be tested after the geopolymer concrete is cured to a corresponding age, which takes a long time. The present invention provides a method for quickly calibrating the strength of geopolymer concrete by pH testing.
[0022] The method for quickly calibrating the strength of geopolymer concrete by pH detection in an embodiment of the present invention comprises the following steps: (1) after mixing the raw materials of geopolymer concrete uniformly to obtain a concrete mixture, taking a first sample from different positions of the concrete mixture; (2) mixing the first sample with water, stirring uniformly, and removing at least part of the aggregate in the first sample by sieving to obtain a second sample; (3) stirring the second sample, and standing and stratifying; (4) detecting the pH of the supernatant obtained by standing and stratifying in step (3); and (5) judging the strength of the geopolymer concrete according to the pH value detected in step (4).
[0023] The steps (1) to (5) of the method for rapidly calibrating the strength of geopolymer concrete by pH detection in the embodiment of the present invention can be completed within 20 minutes, which can significantly shorten the required time compared with the method in the prior art that requires curing to a specific age before testing the strength (when the method of the present invention is used for rapid calibration of the 1d strength of geopolymer concrete, the detection time of the geopolymer concrete strength can be shortened to at least 1 / 72 of the original time; correspondingly, when the method of the present invention is used for rapid calibration of the 28d strength of geopolymer concrete, the detection time of the geopolymer concrete strength can be shortened to at least 1 / 2016 of the original time).
[0024] In a preferred embodiment of the present invention, in step (2), the mass ratio of the first sample to water is 1:1-1:5 (for example, 1:1, 1:2, 1:3, 1:4 or 1:5); in step (3), the stirring speed is 1000-1500 r / min (for example, 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min or 1500 r / min), the stirring time is 5-8 min (5 min, 6 min, 7 min or 8 min), and the standing time is 5-10 min (for example, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min).
[0025] In a preferred embodiment of the present invention, in step (1), the number of portions of the first sample is 3-4, and the mass of each portion of the first sample is 50-60 g (for example, 50 g, 52 g, 54 g, 56 g, 58 g or 60 g).
[0026] In a preferred embodiment of the present invention, in step (2), the sieve used for sieving is a standard square hole sieve of 0.15 mm.
[0027] In a preferred embodiment of the present invention, the raw materials of geopolymer concrete include: geopolymer, mineral powder, fly ash, aggregate and water.
[0028] Preferably, the geopolymer includes, by mass, 30-40 parts (e.g., 30, 32, 34, 36, 38 or 40 parts) of mineral powder, 10-30 parts (e.g., 10, 14, 18, 22, 26 or 30 parts) of fly ash, 10-30 parts (e.g., 10, 14, 18, 22, 26 or 30 parts) of gypsum, 0-30 parts (e.g., 0, 5, 10, 15, 20, 25 or 30 parts) of red mud and 0.1-5 parts (e.g., 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5 parts) of alkali slag.
[0029] Preferably, in step (5), the closer the pH value is to 12, the greater the strength of the geopolymer concrete.
[0030] More preferably, the geopolymer comprises 35 parts of mineral powder, 29 parts of fly ash, 25 parts of gypsum, 10 parts of red mud and 1 part of alkali slag in terms of mass fraction; after the pH value obtained by detection in step (4), the strength of the geopolymer concrete is determined according to the following Table 1: Table 1 Comparison table of pH value range and strength of geopolymer concrete
[0031] Note: Table 1 is the rules summarized from a large number of laboratory verifications and actual product production testing processes.
[0032] In a preferred embodiment of the present invention, the aggregate includes machine-made sand, fine sand, pebbles and large stones; the machine-made sand is coarse sand in zone I, the fine sand is extra-fine sand in zone III, the particle size of the pebbles is ≤5 mm, and the particle size of the large stones is 10-20 mm.
[0033] In a preferred embodiment of the present invention, the raw materials of geopolymer concrete also include a water reducing agent.
[0034] In a preferred embodiment of the present invention, the concrete mixture is prepared by a method comprising the following steps: A. adding geopolymer, mineral powder, fly ash and aggregate into a concrete mixer for dry mixing, stirring for 1-2 minutes to obtain a dry mixture; B. adding water to the dry mixture, stirring for 2-3 minutes to obtain a concrete mixture.
[0035] In a preferred embodiment of the present invention, in step B, a step of adding a water reducing agent is also included before stirring.
[0036] The method for quickly calibrating the strength of geopolymer concrete by pH detection of the present invention is described in detail below through specific examples.
[0037] Example 1 The design strength grade of the geopolymer concrete to be tested in this embodiment is C30; the raw materials of each cubic meter of geopolymer concrete include: 165kg of water, 210kg of geopolymer, 70kg of mineral powder, 85kg of fly ash, 6kg of polycarboxylic acid water reducer, 560kg of machine-made sand, 240kg of fine sand, 160kg of small stones and 900kg of large stones.
[0038] The geopolymer consists of 35 parts of mineral powder, 29 parts of fly ash, 25 parts of gypsum, 10 parts of red mud and 1 part of alkali slag.
[0039] In this embodiment: the mineral powder adopts S95 grade mineral powder produced by Jiyuan Guotai Micropowder Technology Co., Ltd.; the fly ash adopts Grade II fly ash produced by China Resources Power (Jiaozuo) Co., Ltd.; the coarse and fine aggregates are both provided by Jiaozuo Qianye New Materials Co., Ltd., among which the machine-made sand is coarse sand in Zone I, the fine sand is extra-fine sand in Zone III, the small stones are ≤5mm in specification, and the large stones are 10~20mm in specification; the water reducer is ordinary polycarboxylic acid water reducer produced by Jiangsu Subote New Materials Co., Ltd.; the gypsum is desulfurized gypsum produced by China Resources Power (Jiaozuo) Co., Ltd.; the red mud is the sintered red mud produced by Zhongzhou Aluminum Plant in April 2024; the alkali slag is the industrial alkali slag produced by Zhongtian Alkali Industry Co., Ltd. in May 2024.
[0040] After the above raw materials (geopolymer, mineral powder, fly ash and aggregate) are prepared according to the ratio, they are added to a concrete mixer for dry mixing, and a dry mixture is obtained after stirring for 1 to 2 minutes; weighed water and polycarboxylate water reducer are slowly added to the dry mixture, and the mixture is continuously stirred for 2 to 3 minutes before being removed from the pot to obtain the geopolymer concrete mixture to be tested in this embodiment.
[0041] The method for quickly calibrating the strength of geopolymer concrete by pH detection in this embodiment includes the following steps (which can be completed within 20 minutes): (1) Samples were taken at different positions of the geopolymer concrete mixture to obtain three 50g first samples, and the remaining geopolymer concrete was put into a mold for molding. Subsequent curing was carried out in accordance with GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the compressive strength of the concrete was tested at 1d, 3d, 7d, and 28d after curing to the corresponding age; (2) The three first samples were independently mixed with ultrapure water at a mass ratio of 1:1, and stirred with a stirring rod for 3 minutes to preliminarily dilute the first samples; (3) The three diluted samples were passed through a standard square hole sieve with a size of 0.15 mm respectively. The second sample (liquid) that passed through the sieve was placed on a magnetic stirrer and stirred and dispersed at 1500 r / min for 5 minutes. Then, the slurry was allowed to stand for 5 minutes to settle and separate. The pH value of the supernatant of the three second samples was then tested using a pH meter. The final pH value of the sample was the average of the three values. (4) The above steps were repeated five times using the same raw materials and proportions. The pH value test results of the five geopolymer concretes were 11.9-12.1 (see Table 2 below for details); (5) According to Table 1 (pH value range calibration strength comparison table of geopolymer concrete), the five groups of 1d strength greater than 10MPa, 3d strength greater than 20MPa, 7d strength greater than 30MPa, and 28d strength greater than 40MPa can be pre-calibrated; the calibration results are compared with the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured in step (1) according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (see Table 2 below for details).
[0042] Table 2 pH value of concrete and compressive strength at different ages
[0043] The results in Table 2 show that when the pH value of the sample is in the range of 11.90 to 12.10, the actual measured compressive strength of the concrete is consistent with the result pre-calibrated according to the method of the present invention. It can be explained that the rapid calibration method of the present invention can accurately calibrate the strength development of geopolymer concrete, and the closer the pH value is to 12, the higher its strength.
[0044] Example 2 The raw materials and proportions of the geopolymer concrete to be tested in this embodiment are the same as those in Example 1, except that the sources of the mineral powder and fly ash raw materials of the geopolymer are different (the remaining raw materials except the mineral powder and fly ash are also the same as those in Example 1; this embodiment and Example 1 were carried out on the same day), specifically: In this embodiment: the mineral powder adopts the S95 grade mineral powder provided by Shanxi Jincheng Iron and Steel Holding Group Co., Ltd.; the fly ash adopts the grade II fly ash provided by Jiaozuo Wanfang Electric Power Co., Ltd.
[0045] The method for quickly calibrating the strength of geopolymer concrete by pH detection in this embodiment comprises the following steps: (1) Take three 50g first samples at different positions of the geopolymer concrete mixture (prepared in the same way as in Example 1), and put the remaining geopolymer concrete mixture into a mold for molding. After subsequent curing to the age according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", test the compressive strength of the concrete at 1d, 3d, 7d, and 28d; (2) The three first samples were independently mixed with ultrapure water at a mass ratio of 1:1, and stirred with a stirring rod for 3 minutes to preliminarily dilute the first samples; (3) The three diluted samples were passed through a standard square hole sieve with a size of 0.15 mm. The second sample (liquid) that passed through the sieve was placed on a magnetic stirrer and dispersed and stirred at 1500 r / min for 5 minutes. The slurry was then allowed to stand for 5 minutes to settle and separate. The pH value of the supernatant of the three second samples was then tested using a pH meter. The final pH value of the sample was the average of the three values. (4) The above steps were repeated five times using the same raw materials and proportions. The pH test results of the five geopolymer concretes were 12.10<pH<12.50. According to Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the five groups of 1d strength greater than 5MPa, 3d strength greater than 10MPa, 7d strength greater than 25MPa, and 28d strength greater than 30MPa can be pre-calibrated. The calibration results were compared with the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured in step (1) according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (see Table 3 below for details).
[0046] Table 3 pH value of concrete and compressive strength at different ages
[0047] The results show that when the pH value of the sample is in the range of 12.10-12.50, the actual measured 1d, 3d, 7d, and 28d compressive strength of the concrete are consistent with the results pre-calibrated according to the rapid calibration method of the present invention. Therefore, it can be known that the strength rapid calibration method can successfully calibrate the strength development of geopolymer concrete, and then the raw materials of different manufacturers can be screened by adopting the rapid calibration method of the present invention.
[0048] Example 3 The difference between this embodiment and embodiment 1 is that: the S95 grade mineral powder produced by Jiyuan Guotai Micro Powder Technology Co., Ltd. and the desulfurized gypsum produced by China Resources Power (Jiaozuo) Co., Ltd. are used to prepare the geopolymer of this embodiment after being purchased and placed for two months (the batches of mineral powder and desulfurized gypsum used in this embodiment are different from those in embodiment 1); the source, batch and dosage ratio of the remaining raw materials are consistent with the geopolymer concrete of embodiment 1 (this embodiment and embodiment 1 are carried out on the same day).
[0049] According to the method of Example 1, the pH and compressive strength of the corresponding geopolymer concrete mixture were tested respectively (the test was repeated five times, and the average value of the test results of each time was taken as 3 samples); the pH values obtained from the five tests were in the range of 11.5-11.9 (see Table 4 below for details); according to the above Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the 1d strength of the five groups can be pre-calibrated to be greater than 5MPa, the 3d strength is greater than 10MPa, the 7d strength is greater than 15MPa, and the 28d strength is greater than 30MPa; the calibration results are compared with the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured in step (1) according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (see Table 4 below for details).
[0050] Table 4 pH value of concrete and compressive strength at different ages
[0051] The results show that when the pH value of the sample is in the range of 11.50 to 11.90, the actual measured 1d, 3d, 7d, and 28d concrete compressive strength of the concrete is consistent with the results pre-calibrated according to the rapid calibration method of the present invention. Therefore, it can be known that the strength rapid calibration method of the present invention can successfully calibrate the strength development of geopolymer concrete; in addition, the strength rapid calibration method of the present invention also helps to conveniently monitor the quality of the purchased raw materials, which helps to ensure the quality stability of geopolymer concrete or select suitable raw materials according to the strength requirements of different application scenarios to avoid waste of raw materials.
[0052] Example 4 The raw materials and proportions of the geopolymer in this embodiment, as well as the raw material proportions of the geopolymer concrete to be tested are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the manufacturer and batch number of the mineral powder, fly ash, gypsum, red mud and alkali slag used in the geopolymer in this embodiment are the same as those in Example 1, but the storage time is extended by 2 months compared with Example 1.
[0053] According to the method of Example 1, the pH and compressive strength of the corresponding geopolymer concrete mixture were tested respectively (the test was repeated five times, and the average value of the test results of each time was taken as 3 samples); the pH values obtained from the five tests were in the range of 11.00-11.50 (see Table 5 below for details); according to Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the 1d strength of the five groups can be pre-calibrated to be greater than 2MPa, the 3d strength is greater than 10MPa, the 7d strength is greater than 12MPa, and the 28d strength is greater than 25MPa; the calibration results are compared with the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured in step (1) according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (see Table 5 below for details).
[0054] Table 5 pH value of concrete and compressive strength at different ages
[0055] The results show that when the pH value of the sample is within the range of 11.00 to 11.50, the 1d, 3d, 7d, and 28d compressive strengths of the concrete actually measured are consistent with the results pre-calibrated according to the rapid calibration method of the present invention. Therefore, it can be seen that the rapid strength calibration method can successfully calibrate the development of geopolymer concrete, and the influence of the quality change of the product after long-term packaging and storage on the compressive strength of geopolymer concrete can be predicted by using the rapid calibration method of the present invention. In addition, it can be seen from this embodiment that after the storage time of the raw materials of the geopolymer is extended for two months, the strength calibration is performed again, and the raw material performance will have a certain failure, thereby showing a decrease in pH value.
[0056] Example 5 The raw materials and proportions of the geopolymer concrete to be tested in this embodiment are the same as those in Example 1, but the sources of the mineral powder, fly ash, and gypsum raw materials of the geopolymer are different from those in Example 1 (this embodiment and Example 1 were carried out on the same day), specifically: Among them, the mineral powder uses S95 grade mineral powder provided by Shanxi Jincheng Iron and Steel Holding Group Co., Ltd.; the fly ash uses Class II fly ash provided by Jiaozuo Wanfang Electric Power Co., Ltd., and the gypsum uses desulfurization gypsum provided by Qinbei Power Plant of Huaneng International Power Co., Ltd.
[0057] According to the method of Example 1, the pH and compressive strength of the corresponding geopolymer concrete mixture were tested respectively (the test was repeated five times, and the average value of the test results of each time was taken as 3 samples); the pH values obtained from the five tests were in the range of 12.50-12.90 (see Table 6 below); according to Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the 1d strength of the five groups can be pre-calibrated to be greater than 3MPa, the 3d strength is greater than 10MPa, the 7d strength is greater than 20MPa, and the 28d strength is greater than 25MPa; the calibration results are compared with the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured in step (1) according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (see Table 6 below).
[0058] Table 6 pH value of concrete and compressive strength at different ages
[0059] The results show that the pH values of the samples are all within the range of 12.50-12.90, and the actual measured 1d, 3d, 7d, and 28d compressive strengths of the concrete are consistent with the results pre-calibrated according to the rapid calibration method of the present invention. Therefore, it can be known that the strength rapid calibration method can successfully calibrate the strength development of geopolymer concrete; in addition, the strength rapid calibration method of the present invention also helps to conveniently monitor the quality of the purchased raw materials, which helps to ensure the quality stability of geopolymer concrete or select appropriate raw materials according to the strength requirements of different application scenarios to avoid waste of raw materials.
[0060] Example 6 The raw materials and proportions of the geopolymer concrete to be tested in this embodiment are the same as those in Example 1 (this embodiment and Example 1 were carried out on the same day). In order to verify the accuracy of the method of the present invention, two portions of the geopolymer used in Example 1 were taken, and different proportions of alkali slag were added to each of them. After each of them was fully mixed, three samples were randomly taken from each of the two geopolymers to obtain a total of six geopolymer samples (the addition ratio of alkali slag in 6-1, 6-2 and 6-3 was 0.2%, that is, the amount of alkali slag in 6-1, 6-2 and 6-3 was 100.2% of that in Example 1; the addition ratio of alkali slag in 6-3, 6-4 and 6-5 was 0.4%, that is, 100.4% of the alkali slag in 6-3, 6-4 and 6-5).
[0061] According to the method of Example 1, the above six parts of geopolymers are respectively applied to the preparation of geopolymer concrete (except for the different amounts of alkali slag in the geopolymer, the rest are consistent with Example 1), and the geopolymer concrete is treated according to the method of Example 1 (after obtaining the concrete mixture, sampling is taken, and the remaining concrete mixture is put into a mold for molding, and subsequent curing is carried out in accordance with GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and after curing to the corresponding age, the compressive strength of the concrete is tested at 1d, 3d, 7d, and 28d), and the pH is tested after obtaining the second sample; The corresponding tests of the above six geopolymer concretes were repeated 5 times to obtain the average values, as shown in Table 7 below: Table 7 pH value of concrete and compressive strength at different ages
[0062] The results show that the pH values of samples 6-1, 6-2 and 6-3 are in the range of 12.10-12.50. According to Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the 1d strength of the corresponding geopolymer concrete can be pre-calibrated to be greater than 5MPa, the 3d strength is greater than 10MPa, the 7d strength is greater than 25MPa, and the 28d strength is greater than 30MPa. The pre-calibration results are compared with the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured in step (1) according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". It can be seen that the pre-calibration results according to the rapid calibration method of the present invention are consistent with the actually measured 1d, 3d, 7d, and 28d compressive strengths of the concrete.
[0063] The pH values of samples 6-4, 6-5 and 6-6 are in the range of 12.50 to 12.90. According to Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the 1d strength of the corresponding geopolymer concrete can be pre-calibrated to be greater than 3MPa, 3d strength is greater than 10MPa, 7d strength is greater than 20MPa, and 28d strength is greater than 25MPa. The calibration results are compared with the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured in step (1) according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". It can be seen that the pre-calibrated results according to the rapid calibration method of the present invention are consistent with the actually measured 1d, 3d, 7d, and 28d compressive strengths of the concrete.
[0064] It shows that the method for quickly calibrating the strength of geopolymer concrete by pH detection of the present invention can successfully calibrate the strength development of geopolymer concrete.
[0065] Example 7 The raw materials and proportions of the geopolymer concrete to be tested in this embodiment are the same as those in Example 1. In order to verify the accuracy of the method of the present invention, three portions of the geopolymer used in Example 1 are randomly taken, which are recorded as A; at the same time, according to the proportion of the geopolymer used in Example 1, the amount of alkali slag is reduced to one-fourth of the original amount, and three geopolymer samples are re-prepared, which are recorded as B (this embodiment is carried out on the same day as Example 1).
[0066] The pH and compressive strength of the concrete prepared by geopolymer A and B were tested according to the method of Example 1; the geopolymer concrete of each ratio was tested 5 times according to the method of Example 1 and the average value was taken. The test results within the calibration range are shown in Table 8 below: Table 8 pH value of concrete and compressive strength at different ages
[0067] By comparing the pH values of A and B with Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the later strength of six groups of samples can be pre-calibrated: the pH value of Group A is in the range of 11.90~12.10. According to Table 1, the 1d strength of these three groups can be pre-calibrated to be greater than 10MPa, the 3d strength is greater than 20MPa, the 7d strength is greater than 30MPa, and the 28d strength is greater than 40MPa; the pH values of Group B are all below 11. According to Table 1, these three groups can be pre-calibrated as unqualified.
[0068] According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 1d, 3d, 7d and 28d concrete compressive strengths of the concrete actually measured are shown in Table 7; by comparing the pre-calibrated results according to the method of the present invention with the actually measured compressive strength of the concrete, it can be seen that the method of the present invention for quickly calibrating the strength of geopolymer concrete by pH detection can successfully calibrate the strength development of geopolymer concrete.
[0069] Example 8 The raw materials and proportions of the geopolymer concrete to be tested in this embodiment are the same as those in Example 1. In order to verify the accuracy of the method of the present invention, according to the proportion of the geopolymer used in Example 1, the amount of alkali slag is reduced to one-third and one-half of the original, respectively, to obtain two geopolymers, and then three samples are randomly taken from each of them, to obtain a total of six geopolymer samples (this embodiment and Example 1 are carried out on the same day).
[0070] The pH and compressive strength of six geopolymer concretes were tested according to the method of Example 1; each geopolymer concrete was tested 5 times according to the method of Example 1 and the average value was taken. The test results within the calibration range are shown in Table 9 below: Table 9 pH value of concrete and compressive strength at different ages
[0071] According to the pH values of the six samples and Table 1 (calibrated strength comparison table of pH value range of geopolymer concrete), the later strength of the six groups can be pre-calibrated: the pH values of samples 8-1, 8-2 and 8-3 are in the range of 11.00~11.50. According to Table 1, the 1d strength of these three groups can be pre-calibrated to be greater than 2MPa, the 3d strength is greater than 10MPa, the 7d strength is greater than 12MPa, and the 28d strength is greater than 25MPa; the pH values of samples 8-4, 8-5 and 8-6 are in the range of 11.50~11.90. According to Table 1, the 1d strength of these three groups can be pre-calibrated to be greater than 5MPa, the 3d strength is greater than 10MPa, the 7d strength is greater than 15MPa, and the 28d strength is greater than 30MPa.
[0072] According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 1d, 3d, 7d, and 28d concrete compressive strengths of the concrete actually measured are shown in Table 9; by comparing the pre-calibrated results according to the method of the present invention with the actually measured compressive strength of the concrete, it can be seen that the method of the present invention for quickly calibrating the strength of geopolymer concrete by pH detection can successfully calibrate the strength development of geopolymer concrete.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for rapidly calibrating the strength of geopolymer concrete by pH detection, characterized in that: The steps include: (1) after the raw materials of the geopolymer concrete are uniformly mixed to obtain a concrete mixture, taking a first sample from different positions of the concrete mixture; (2) mixing the first sample with water, stirring evenly, and sieving to remove at least part of the aggregate in the first sample to obtain a second sample; (3) stirring the second sample, allowing it to stand for stratification, and obtaining a supernatant; (4) detecting the pH value of the supernatant; (5) Determine the strength of the geopolymer concrete according to the pH value detected in step (4).
2. The method for rapidly calibrating the strength of geopolymer concrete by pH detection as claimed in claim 1, characterized in that: In step (2), the mass ratio of the first sample to water is 1:1-1:5; In step (3), the stirring speed is 1000-1500 r / min, the stirring time is 5-8 min, and the standing time is 5-10 min.
3. The method for rapidly calibrating the strength of geopolymer concrete by pH detection as claimed in claim 1, characterized in that: In step (1), the number of portions of the first sample is 3-4, and the mass of each portion of the first sample is 50-60 g.
4. The method for rapidly calibrating the strength of geopolymer concrete by pH detection as claimed in claim 1, characterized in that: In step (2), the sieve used for sieving is a standard square hole sieve of 0.15 mm.
5. The method for rapidly calibrating the strength of geopolymer concrete by pH detection according to any one of claims 1 to 4, characterized in that: The raw materials of the geopolymer concrete include: geopolymer, mineral powder, fly ash, aggregate and water.
6. The method for rapidly calibrating the strength of geopolymer concrete by pH detection as claimed in claim 5, characterized in that: The aggregate includes machine-made sand, fine sand, small stones and large stones; The machine-made sand is coarse sand in zone I, the fine sand is extra-fine sand in zone III, the particle size of the small pebbles is ≤5mm, and the particle size of the large pebbles is 10-20mm.
7. The method for rapidly calibrating the strength of geopolymer concrete by pH detection as claimed in claim 5, characterized in that: The raw materials of the geopolymer concrete also include a water reducing agent.
8. The method for rapidly calibrating the strength of geopolymer concrete by pH detection as claimed in claim 5, characterized in that: The concrete mixture is prepared by a method comprising the following steps: A. adding the geopolymer, mineral powder, fly ash and aggregate into a concrete mixer for dry mixing, stirring for 1-2 minutes to obtain a dry mix; B. Add water to the dry mix and stir for 2-3 minutes to obtain the concrete mixture.
9. The method for rapidly calibrating the strength of geopolymer concrete by pH detection as claimed in claim 5, characterized in that: In step B, a step of adding a water reducing agent is also included before stirring.
Citation Information
Patent Citations
Method for in-situ detecting quality of deep-cement-mixed soil based on mixing uniformity
CN1766642A
Modified soil strength prediction method
JP2015074914A
Soil cement strength evaluation kit
JP3214585U
Specimen curing apparatus for early measuring strength test of hardening concrete and the method by using the same
KR1020030017141A